Design, Synthesis, and Biological Evaluation of Novel Thiazolidinone-Containing Quinoxaline-1,4-di-N-oxides as Antimycobacterial and Antifungal Agents - Zhang, Heying; Zhang, Jie; Qu, Wei; Xie, Shuyu; Huang, Lingli; Chen, Dongmei; Tao, Yanfei; Liu, Zhenli; Pan, Yuanhu; Yuan, Zonghui (Frontiers in Chemistry, 2020)
A series of novel quinoxaline-1,4-di-N-oxides containing thiazolidinone moiety were designed and synthesized and their antimycobacterial activities were evaluated. Among them, compounds 2t, 2u, 2y and 2z displayed the most potent antimycobacterial activity against Mtb H37Rv strain (MIC = 1.56 μg/mL). All the compounds were also evaluated antifungal activity against Candida albicans, C. tropicalis, A. fumigatus and C. neoformans. Compounds 2t, 2u, 2y and 2z exhibited potential antifungal activities, having MIC between 2-4 μg/mL. CoMFA (q2=0.914, r2=0.967) and CoMSIA (q2=0.918, r2=0.968) models were established to investigate the structure and antimycobacterial activity relationship. The results of contour maps revealed that electronegative and sterically bulky substituents play an important role in the antimycobacterial activity. Electronegative and sterically bulky substituents are preferred in C7 position of the quinoxaline ring and C4 position of phenyl group to increase the antimycobacterial activity. Additionally, more hydrogen bond donor substituents should be considered at C2 side chain of the quinoxaline ring to improve the activity of compounds.